Using dental and activity indicators in order to explore possible sex differences in an adult rural medieval population from Thebes (Greece) - Michael, Dimitra Ermioni; Iliadis, Efstathios; Manolis, Sotiris K. (Anthropological Review, 2017)
Assessing the subsistence strategies of past populations; through their dietary and occupational patterns; could provide important information regarding social status and possible gender differences, especially in turbulent historical periods, as the one of the Crusader’s occupation in Greece (1204-1460 AD). Therefore, the human sample from Aghia Triada in Thebes (13th-14th c. AD) serves as the ideal skeletal material. Diet was explored through two dental indicators; dental caries and tooth wear, while occupational stress was explored through three activity markers; osteoarthritis (OA), spinal facet remodeling and Schmorl’s nodes. The aims of the present study are to assess the dietary and activity patterns of the stated population and explore possible sex differentiations. A total of 126 teeth and 350 vertebrae have been examined. The entire population presents a caries rate of 16.7%, and males present a much higher caries frequency than females (25.5% males vs. 9.9% females). Furthermore, females present significantly higher rates of osteophytes than males, whereas no significant sex differences were found regarding facet remodeling and Schmorl’s nodes. Dental results confirm historical information of medieval Thebes having an agricultural economy and are also in agreement with isotopic data. In addition, our findings suggest very intense physical activity for both sexes, whereas the distribution of facet remodeling along the spine could indicate a possible gender division of labor. Our study proposes two positive correlations; between facet remodeling and osteophytes, and between Schmorl’s nodes and facet remodelling; as activity indicators in past or/and modern populations. Finally, we strongly encourage the inclusion of spinal facet remodelling in studies focusing on occupational stress.